Die Vergnügungen der anderen: Fachsensible Hochschuldidaktik als neuer Weg zwischen allgemeiner und fachspezifischer Hochschuldidaktik - Scharlau, Ingrid; Keding, Gesche (Pädagogische Hochschulentwicklung: von der Programmatik zur Implementierung)

Sich gar nicht erst im behaglichen Zuhause der eignen Disziplin einrichten: Eine fachfremde Hausarbeit im ersten Semester - Scharlau, Ingrid; Heß, Christiane (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

And now for something completely different - Lehren und Lernen angesichts digitaler Herausforderungen - Scharlau, Ingrid (Bildung und Hochschule: Impulse für Studium und Lehre am Beispiel des Leuphana College)

Mathematik schreiben - Scharlau, Ingrid (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2014)

Drei Einflüsse auf Schreibberatung und ein integriertes Modell der Selbststeuerung für Schreibberaterinnen und Schreibberater - Keding, Gesche; Scharlau, Ingrid (Schreibberatung und Schreibförderung. Impulse aus Theorie, Empirie und Praxis)

Reading mathematical texts with philosophical methods - Schnieder, Jörn; Scharlau, Ingrid (Special Issue: The Philosophy of Mathematics Education at ICME 13)
The paper presents a hermeneutic approach to teaching and learning mathematics in which the hermeneutic circle is translated into methods of reading mathematical texts with the help of the three decisive steps 1) making prior knowledge explicit, 2) interpreting texts, and 3) fusing horizons of prior understanding and text content.

Zwei Fenster mit verschiedener Sicht - Scharlau, Ingrid; Karsten, Andrea; Nettingsmeier, Pia; Golombek, Christiane; Schäfer, Stefanie (Akademisches Schreiben. Halbband 1: Vom Qualitätspakt Lehre geförderte Schreibzentren und Schreibwerkstätten)

Does attention speed up processing? Decreases and increases of processing rates in visual prior entry. - Tünnermann, Jan; Petersen, Anders; Scharlau, Ingrid (Journal of Vision)
Selective visual attention improves performance in many tasks. Among others, it leads to 'prior entry'—earlier perception of an attended compared to an unattended stimulus. Whether this phenomenon is purely based on an increase of the processing rate of the attended stimulus or if a decrease in the processing rate of the unattended stimulus also contributes to the effect is, up to now, unanswered. Here we describe a novel approach to this question based on Bundesen’s Theory of Visual Attention, which we use to overcome the limitations of earlier prior-entry assessment with temporal order judgments (TOJs) that only allow relative statements regarding the processing speed of attended and unattended stimuli. Prevalent models of prior entry in TOJs either indirectly predict a pure acceleration or cannot model the difference between acceleration and deceleration. In a paradigm that combines a letter-identification task with TOJs, we show that indeed acceleration of the attended and deceler
Keywords: unattended stimuli; attention speed; cognitive processing; Attention; Humans; Judgment; Mental Recall; Visual Perception; Stimulus Parameters; Visual Perception; Visual Attention; Cognitive Processes; Velocity

Fachsensible Hochschuldidaktik - Scharlau, Ingrid (Teaching is touching the future: Academic teaching within and across disciplines)

Nur Zahlen und Zeichen? Zum Nutzen des Schreibens in der Hochschuldidaktik der Mathematik - Scharlau, Ingrid; Heß, Christiane; Schnieder, Jörn (Neues Handbuch Hochschullehre. 70. Ergänzungslieferung)

Reflection on the Leitmotif "Wrapped in Code" - Scharlau, Ingrid

Schreiben im Blick. Schriftliche Formen der sprachlichen Tätigkeit aus dialogischer Perspektive - Karsten, Andrea

Writing: Movements of the self - Karsten, Andrea (Theory & Psychology)
This article presents analyses of excerpts from a study on writing conducted in a dialogical perspective. The study’s material was collected by the auto-confrontation method: writers were videotaped during their work and afterwards confronted with their writing activities. Microanalysis of the material attends to how inner dialogues during writing are “refracted” (Voloshinov) in auto-confrontation. Bakhtin’s notion of the chronotope (time-and-space) as the main tool of analysis helps to discern the changing contexts and position constellations utterances are valid for. It thus sheds light on the positioning movements performed by the writing selves through language. The analyses show various utterance movements traversing the chronotopes involved, ranging from refractions of movements between the writers’ inner dialogues and their texts to retrospective imperatives with a developmental potential. This “dialogical volume” of speech activity presenting itself in writing can contribute to our understanding of the interplay of language and the self.
Keywords: auto-confrontation; chronotope; inner dialogue; microanalysis; positioning; writing

Schreiben ist Dialog. Ergebnisse und Implikationen einer Studie zum ,schreibbegleitenden‘ Sprechen - Karsten, Andrea (JoSch – Journal der Schreibberatung)

Erwerb mathematischer Schreibkompetenz während der Studieneingangsphase - Scharlau, Ingrid; Schnieder, Jörn (Beiträge zum Mathematikunterricht 2014)

Textilien - Eine Beobachtung - Scharlau, Ingrid (Kleppart - Ausstellungen 2010-2013)

Humboldt revisited - forschend lehren - lehrend forschen - Keding, Gesche; Scharlau, Ingrid (Greifswalder Beiträge zur Hochschullehre: Forschendes Lehren und Lernen in der polyvalenten Lehre)

Jean Piaget zur Einführung - Scharlau, Ingrid

Studium und Beruf: Studienstrategien - Praxiskonzepte - Professionsverständnis. Perspektiven von Studierenden und Lehrenden nach der Bologna-Reform

Schreiben: Tipps, Anregungen und Strategien für das Schreiben am Leuphana College - Scharlau, Ingrid; Heß, Christiane; Vierck, Sigrid; Bluhm, Clara

Self-Assessment-Instrumente: Eine Möglichkeit der Bildung, Reflexion und Ausdifferenzierung von Subjektiven Theorien - Scharlau, Ingrid; Bunte, Nicola; Wiescholek, Sabrina (Studium und Beruf: Studienstrategien - Praxiskonzepte – Professionsverständnis. Perspektiven von Studierenden und Lehrenden nach der Bologna-Reform)
Unter Bezugnahme auf Erkenntnisse, die im Rahmen des Projekts STEP (Studium und Beruf: Subjektive Theorien von Studierenden und Lehrenden zwischen Praxisbezug, Employability und Professionalisierung) gewonnen wurden, wird nach der Möglichkeit der Bildung, Reflexion und Ausdifferenzierung von Subjektiven Theorien durch Self-Assessments gefragt. Inhalte wie Strukturiertheit und Theorieförmigkeit der Vorstellungen (Vernetzungen, schlussfolgernd-argumentativer Charakter) erwiesen sich in der Untersuchung als deutlich veränderungsbedürftig. Es wird argumentiert, dass eine inhaltliche Anreicherung oder Restrukturierung vorhandener Überzeugungen die Ausbildung großer und komplexer Überzeugungssysteme vorausetzt. Maßnahmen, die an den individuellen Vorstellungen, deren Bewusstmachung und Reflexion ansetzen, werden vorgestellt.

A New Model of Higher Education in the European Context - The Leuphana Experience - Gunkel, Marjaana; Schütz, Julia; Seifert, Andreas; Scharlau, Ingrid; Beck, Karin; Heuer, Claudia (INTED2013 Conference Proceedings)

Ringen um Sinn. Subjektive Theorien von Lehramtsstudierenden zum Praxisbezug des Studiums. - Scharlau, Ingrid; Wiescholek, Sabrina (Studium und Beruf: Studienstrategien - Praxiskonzepte - Professionsverständnis. Perspektiven von Studierenden und Lehrenden nach der Bologna-Reform)

Was also ist gleichzeitig? Allgemeinpsychologische Anmerkungen zur Wahrnehmung von Gleichzeitigkeit - Scharlau, Ingrid; Weiß, Katharina (Simultaneität)

Attention and the Speed of Information Processing: Posterior Entry for Unattended Stimuli Instead of Prior Entry for Attended Stimuli - Weiß, Katharina; Hilkenmeier, Frederic; Scharlau, Ingrid (PLoS ONE)
Why are nearly simultaneous stimuli frequently perceived in reversed order? The origin of errors in temporal judgments is a question older than experimental psychology itself. One of the earliest suspects is attention. According to the concept of prior entry, attention accelerates attended stimuli; thus they have “prior entry” to perceptive processing stages, including consciousness. Although latency advantages for attended stimuli have been revealed in psychophysical studies many times, these measures (e.g. temporal order judgments, simultaneity judgments) cannot test the prior-entry hypothesis completely. Since they assess latency differences between an attended and an unattended stimulus, they cannot distinguish between faster processing of attended stimuli and slower processing of unattended stimuli. Therefore, we present a novel paradigm providing separate estimates for processing advantages respectively disadvantages of attended and unattended stimuli. We found that deceleration of unattended stimuli contributes more strongly to the prior-entry illusion than acceleration of attended stimuli. Thus, in the temporal domain, attention fulfills its selective function primarily by deceleration of unattended stimuli. That means it is actually posterior entry, not prior entry which accounts for the largest part of the effect.

Prior entry and temporal attention: Cueing affects order errors in RSVP. - Hilkenmeier, Frederic; Olivers, Christian N. L.; Scharlau, Ingrid (Journal of Experimental Psychology: Human Perception and Performance)
The law of prior entry states that attended objects come to consciousness more quickly than unattended ones. This has been well established in spatial cueing paradigms, where two task-relevant stimuli are presented near-simultaneously at two different locations. Here, we suggest that prior entry also plays a pivotal role in temporal attention paradigms, where stimuli appear at the same location but at distinct moments in time, in rapid serial presentation (RSVP). Specifically, we hypothesize that prior entry can explain temporal order reversals in reporting two targets from RSVP. In support of this, three experiments show that cueing attention toward either of the targets has a strong influence on order errors. We conclude that prior entry provides a viable explanation of the way in which relevant information is prioritized in RSVP. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: attentional blink; attentional enhancement; lag-1 sparing; prior entry; temporal cueing; visual attention; rapid serial presentation; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Female; Humans; Male; Neuropsychological Tests; Pattern Recognition; Visual; Time Factors; Visual Perception; Young Adult; Cues; Serial Recall; Visual Attention; Eyeblink Reflex

At the mercy of prior entry: Prior entry induced by invisible primes is not susceptible to current intentions. - Weiß, Katharina; Scharlau, Ingrid (Acta Psychologica)
If one of two events is attended to, it will be perceived earlier than a simultaneously occurring unattended event. Since 150 years, this effect has been ascribed to the facilitating influence of attention, also known as prior entry. Yet, the attentional origin of prior-entry effects¹ has been repeatedly doubted. One criticism is that prior-entry effects might be due to biased decision processes that would mimic a temporal advantage for attended stimuli. Although most obvious biases have already been excluded experimentally (e.g. judgment criteria, response compatibility) and prior-entry effects have shown to persist (Shore, Spence, & Klein, 2001), many other biases are conceivable, which makes it difficult to put the debate to an end. Thus, we approach this problem the other way around by asking whether prior-entry effects can be biased voluntarily. Observers were informed about prior entry and instructed to reduce it as far as possible. For this aim they received continuous feedback
Keywords: intentions; events; attention; decision processes; Adult; Attention; Choice Behavior; Cues; Female; Humans; Intention; Judgment; Male; Middle Aged; Reaction Time; Time Perception; Visual Perception; Attention; Decision Making; Experiences (Events); Intention

Spatial mislocalization as a consequence of sequential coding of stimuli. - Priess, Heinz-Werner; Scharlau, Ingrid; Becker, Stefanie I.; Ansorge, Ulrich (Attention, Perception, & Psychophysics)
In three experiments, we tested whether sequentially coding two visual stimuli can create a spatial misperception of a visual moving stimulus. In Experiment 1, we showed that a spatial misperception, the flash-lag effect, is accompanied by a similar temporal misperception of first perceiving the flash and only then a change of the moving stimulus, when in fact the two events were exactly simultaneous. In Experiment 2, we demonstrated that when the spatial misperception of a flash-lag effect is absent, the temporal misperception is also absent. In Experiment 3, we extended these findings and showed that if the stimulus conditions require coding first a flash and subsequently a nearby moving stimulus, a spatial flash-lag effect is found, with the position of the moving stimulus being misperceived as shifted in the direction of its motion, whereas this spatial misperception is reversed so that the moving stimulus is misperceived as shifted in a direction opposite to its motion when the c
Keywords: spatial mislocalization; sequential coding; stimulus parameters; Attention; Discrimination (Psychology); Humans; Judgment; Motion Perception; Optical Illusions; Orientation; Pattern Recognition; Visual; Psychophysics; Space Perception; Cognitive Processes; Motion Perception; Perceptual Localization; Spatial Perception; Stimulus Parameters; Consequence

The dynamics of prior entry in serial visual processing. - Hilkenmeier, Frederic; Scharlau, Ingrid; Weiß, Katharina; Olivers, Christian N. L. (Visual Cognition)
An attended stimulus reduces the perceptual latency of a later stimulus at the same location, leading to the intriguing finding that the perceived order between the two is often reversed. This prior-entry effect has been well established in a number of different cueing paradigms, mostly involving spatial attentional shifts. Here we assess the time-course of prior entry when all stimuli appear in rapid serial presentation at one location. Our findings indicate that the size of the attentional enhancement is strongly affected by the stimulus onset asynchrony between cue and target, with a rapid early peak, followed by decay. When task-irrelevant cues are used, the cueing effect on prior entry is short-lived and peaks as early as 50 ms. The benefit extends to about 100 ms when task-relevant cues are employed. These results fit with a straightforward computational model of transient attentional enhancement, peaking about 80 100 ms after stimulus detection. (PsycINFO Database Record (c) 20
Keywords: serial visual processing; prior entry dynamics; cueing paradigms; Cues; Visual Perception; Visual Search

Subjektive Theorien von Musikerinnen und Musikern zum Üben: Ein Beitrag an der Schnittstelle von Kognitionspsychologie - Bunte, Nicola; Scharlau, Ingrid (Popmusikforschung und Musikpädagogik)
This article reports on the findings of a qualitative interview study that investigated the individual ideas about practicing of nine musicians of different musical backgrounds, music genres, instruments, and learning biography. The findings reveal a variety of different aspects that are embedded in argumentative reasoning, and thus are analysed as subjective theories. According to differences in complexity with regards to content and argumentative structure we propose the following typification: 1) physical-technical constriction, 2) technique and interpretation centered type, and 3) creative-congnitive focus. A strict affiliation between these types and musical genre was not found.

Praxis nach Rezept? – Praxisbezug und Professionalität in den subjektiven Theorien von Lehramtsstudierenden - Schüssler, Renate; Keuffer, Josef; Günnewig, Kathrin; Scharlau, Ingrid (Schulpädagogik heute: Reform der Lehrerbildung in Deutschland, Österreich und der Schweiz)

Psychologie in der Lehrerbildung: Didaktische Konzeption zur Förderung von Conceptual Change, Selbstlern- und Reflexionskompetenz - Müsche, Hanna S.; Scharlau, Ingrid (Psychologiedidaktik und Evaluation IX)
Es wird eine psychologiedidaktische Konzeption skizziert, die vorwiegend auf der Basis empirischer Evidenz für das bildungswissenschaftliche Lehramtsstudium an der Universität Paderborn entwickelt wurde. Drei Bausteine greifen ineinander: Im Zentrum steht das problemorientierte Lernen, das durch beispielbasiertes Lernen und forschendes Lernen flankiert wird. Über die Einführung in psychologisches Wissen und Denken hinaus wird mit der Konzeption das Ziel verfolgt, die Studierenden in Conceptual Change-Prozessen, im selbstgesteuerten Lernen und in ihrer Reflexionsfähigkeit zu unterstützen und zu fördern. Insgesamt bewegt sich die Konzeption zwischen den lernpsychologischen Polen von Konstruktion und Instruktion und will sowohl einer Berufsfeldorientierung als auch einer Wissenschaftsorientierung Rechnung tragen.

Evaluierung medizinischer Volumenrendering-Algorithmen durch empirische Studien - Domik, Gitta; Arens, Stephan; Tünnermann, Jan; Scharlau, Ingrid (FIfF-Kommunikation)
Wie gut ist ein Rendering Algorithmus, der Bilder aus Daten generiert, die wiederum als Grundlage für eine medizinische Diagnose verwendet werden? In diesem Beitrag werden einerseits beispielhaft empirische Studien und ihre Ergebnisse vorgestellt, die solche Fragestellungen beantworten. Andererseits widmen wir uns auch der generellen Frage, welche Herausforderungen gemeistert werden müssen, um empirische Studien aufzustellen, die in Bezug auf korrekte medizinische Diagnosen und ihre zugrunde liegenden Rendering-Algorithmen sinnvoll sind.
Keywords: Informatik; Visualisierung; Psychologie; Experimentaldesign

Praxis nach Rezept? – Praxisbezug und Professionalität in den subjektiven Theorien von Lehramtsstudierenden - Schüssler, Renate; Keuffer, Josef; Günnewig, Kathrin; Scharlau, Ingrid (Reform der Lehrerbildung in Deutschland, Österreich und der Schweiz. Teil I: Analyse, Perspektiven und Forschung)

Chronotopes in Writing. Excerpts from a Case Study. - Karsten, Andrea (Tätigkeitstheorie – Journal für tätigkeitstheoretische Forschung in Deutschland (Activity Theory – Journal of Activity-Theoretical Research in Germany))

Wie sehen Studierende das Verhältnis von Studium und Beruf? Praxisbezug und Professionalität in den Subjektiven Theorien Studierender - Oechsle, Mechthild; Scharlau, Ingrid; Hessler, Gudrun; Günnewig, Kathrin (Der Bologna-Prozess aus Sicht der Hochschulforschung)
Der Beitrag befasst sich mit der Frage, auf welche Weise Studierende die Anforderungen von Wissenschaft und Berufspraxis aufeinander beziehen und welche Subjektiven Theorien sie hierzu entwickeln. Basierend auf einer qualitativen Befragung von Studierenden des Lehramts und der Soziologie rekonstruiert der Beitrag verschiedene Konzepte von Praxisbezug und Professionalität und analysiert mögliche Zusammenhänge zwischen diesen Konzepten. Der Beitrag macht deutlich, dass es neben der (erwartbaren) Heterogenität zwischen den Studiengängen eine erhebliche Heterogenität der entsprechenden Subjektiven Theorien innerhalb der jeweiligen Studiengänge gibt und diskutiert mögliche Schlussfolgerungen für die universitäre Lehre.

Self-Assessment-Instrumente: Eine Möglichkeit der Reflexion und Differenzierung von Subjektiven Theorien - Scharlau, Ingrid (Workshop: Zum Verhältnis von Studium und Berufspraxis. Perspektiven von Lehrenden und Studierenden)

Top-down contingent feature-specific orienting with and without awareness of the visual input. - Ansorge, Ulrich; Horstmann, Gernot; Scharlau, Ingrid (Advances in Cognitive Psychology)
In the present article, the role of endogenous feature-specific orienting for conscious and unconscious vision is reviewed. We start with an overview of orienting. We proceed with a review of masking research, and the definition of the criteria of experimental protocols that demonstrate endogenous and exogenous orienting, respectively. Against this background of criteria, we assess studies of unconscious orienting and come to the conclusion that so far studies of unconscious orienting demonstrated endogenous feature-specific orienting. The review closes with a discussion of the role of unconscious orienting in action control. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual input; awareness; conscious; orientation; visual perception; Awareness; Consciousness States; Perceptual Orientation; Visual Perception; Blindsight

Prior entry explains order reversals in the attentional blink. - Olivers, Christian N. L.; Hilkenmeier, Frederic; Scharlau, Ingrid (Attention, Perception, & Psychophysics)
When two targets are presented in rapid succession, the first target (T1) is usually identified, but the second target (T2) is often missed. A remarkable exception to this 'attentional blink' occurs when T2 immediately follows the first T1, at lag 1. It is then often spared but reported in the wrong order—that is, before T1. These order reversals have led to the hypothesis that 'lag 1 sparing' occurs because the two targets merge into a single episodic representation. Here, we report evidence consistent with an alternative theory: T2 receives more attention than T1, leading to prior entry into working memory. Two experiments showed that the more T2 performance exceeded that for T1, the more order reversals were made. Furthermore, precuing T1 led to a shift in performance benefits from T2 to T1 and to an equivalent reduction in order reversals. We conclude that it is not necessary to assume episodic integration to explain lag 1 sparing or the accompanying order reversals. (PsycINFO Dat
Keywords: attentional blink; order reversals; prior entry; working memory; visual attention; attentional performance; Adolescent; Adult; Attention; Attentional Blink; Color Perception; Cues; Discrimination (Psychology); Female; Humans; Male; Memory; Short-Term; Pattern Recognition; Visual; Psychophysics; Reaction Time; Reversal Learning; Sensory Gating; Serial Learning; Young Adult; Eyeblink Reflex; Stimulus Change; Stimulus Parameters; Visual Attention; Attentional Blink; Short Term Memory

Simultaneity and temporal order perception: Different sides of the same coin? Evidence from a visual prior-entry study. - Weiß, Katharina; Scharlau, Ingrid (The Quarterly Journal of Experimental Psychology)
Attended stimuli are perceived as occurring earlier than unattended stimuli. This phenomenon of prior entry is usually identified by a shift in the point of subjective simultaneity (PSS) in temporal order judgements (TOJs). According to its traditional psychophysical interpretation, the PSS coincides with the perception of simultaneity. This assumption is, however, questionable. Technically, the PSS represents the temporal interval between two stimuli at which the two alternative TOJs are equally likely. Thus it also seems possible that observers perceive not simultaneity, but uncertainty of temporal order. This possibility is supported by prior-entry studies, which find that perception of simultaneity is not very likely at the PSS. The present study tested the percept at the PSS in prior entry, using peripheral cues to orient attention. We found that manipulating attention caused varying temporal perceptions around the PSS. On some occasions observers perceived the two stimuli as sim
Keywords: temporal order perception; simultaneity; temporal order judgment; attention; visual perception; Adolescent; Adult; Attention; Cues; Discrimination (Psychology); Female; Humans; Judgment; Male; Models; Psychological; Photic Stimulation; Reaction Time; Time Factors; Uncertainty; Visual Perception; Young Adult; Attention; Judgment; Stimulus Similarity; Time Perception; Visual Discrimination; Temporal Order (Judgment)

Towards Cultural-Historical and Dialogical Writing Research – Some Methodological Considerations - Karsten, Andrea (Cultural-Historical Psychology)
Based on a cultural-historical and dialogical conceptualization of thinking and speech as formulated in Soviet psychology and linguistics of the 1920s and 1930s, this article seeks to reflect upon a congruent way of investigating writing as a cognitive and communicative activity. What has to be taken into account when developing a methodology for writing research from a cultural-historical and dialogical perspective? Firstly, writing is not separated from other forms of speech activity like interpersonal and intrapersonal speech. Thus, inner dialogue and the addressed character of writing become crucial notions to be methodologically considered. Secondly, contrary to current writing research traditions such as literacy studies and studies of the writing process in cognitive psychology, both individual writing processes and socio-cultural writing practices as well as their relationship must be considered. These reflections lead towards the conclusion that writing is not fully accessible to external observation or to introspection. In consequence, a suggestion of a methodological approach is given, inspired by the activity theoretically informed method of auto-confrontation. The proposed method consists of two phases: a) videotaping of a writing episode and b) co-analysis of the videotaped writing episode in dialogue between writer and researcher. The second phase transfers the writing activity into a new context where understanding it becomes possible. The co-analysis makes involved positions audible: positions of the writer and of the researcher, of real and imagined readers as well as intersubjective and community-related positions. Finally, implications of the proposed research setting are discussed and evaluated with regard to the theoretical grounding. An instance of the methodology to be sketched in this article was developed in the context of the author’s dissertation project in preparation at Ludwig-Maximilians-Universität in Munich, Germany with the working title «Writing processes and writing practices. A conceptualization from a dialogical perspective». The project is funded by scholarships of Universität Bayern e.V. and Ludwig-Maximilians-Universität.
Keywords: writing; writing research; dialogue; dialogical perspective; auto-confrontation

Konzeption von Schreiben - Karsten, Andrea (Tätigkeitstheorie – Journal für tätigkeitstheoretische Forschung in Deutschland (Activity Theory – Journal of Activity-Theoretical Research in Germany))
Ziel dieses Beitrags ist, Vygotskijs Konzeption von Schreiben durch eine genaue Lektüre seiner Texte herauszuarbeiten. Es zeigen sich mit einer entwicklungspsychologischen Herangehensweise zum einen und dem Begriff des schriftlichen Sprechens im Kontext von innerem und äußerem Sprechen zum anderen zwei wesentliche Interessens- und Arbeitsgebiete Vygotskijs im Hinblick auf Schreiben. Dem folgend arbeitet dieser Beitrag zunächst die Überlegungen Vygotskijs zu ontogenetischen Aspekten des Schreibens heraus. Darüber hinaus wird dargestellt, in welcher Beziehung bei Vygotskij „schriftliches Sprechen“ zu den Konzepten des inneren und des äußeren Sprechens steht. Es ergibt sich ein Bild von Schreiben als gleichermaßen kognitivem wie kommunikativem Vorgang. Auf diesen Gedanken Vygotskijs bauen abschließend Überlegungen auf, die Wege für mögliche Weiterentwicklungen von Vygotskijs Konzeption von Schreiben weisen.

Enhancing implicit change detection through action. - Tseng, Philip; Tuennermann, Jan; Roker-Knight, Nancy; Winter, Dorina; Scharlau, Ingrid; Bridgeman, Bruce (Perception)
Implicit change detection demonstrates how the visual system can benefit from stored information that is not immediately available to conscious awareness. We investigated the role of motor action in this context. In the first two experiments, using a one-shot implicit change detection paradigm, participants responded to unperceived changes either with an action (jabbing the screen at the guessed location of a change) or with words (verbal report), and sat either 60 cm or 300 cm (with a laser pointer) away from the display. Our observers guessed the locations of changes at a reachable distance better with an action than with a verbal judgment. At 300 cm, beyond reach, the motor advantage disappeared. In experiment 3, this advantage was also unavailable when participants sat at a reachable distance but responded with hand-held laser pointers near their bodies. We conclude that a motor system specialized for real-time visually guided behavior has access to additional visual information.
Keywords: implicit change detection; action perception; visual system; perceptual judgment; verbal fluency; Analysis of Variance; Awareness; Female; Humans; Male; Psychomotor Performance; Random Allocation; Reaction Time; Visual Perception; Visual Memory; Visual Stimulation; Implicit Memory; Judgment; Perceptual Discrimination

Temporal order judgments: A sensitive measure for measuring perceptual latency? - Weiß, Katharina; Scharlau, Ingrid (Proceedings of the 26th Annual Meeting of the International Society for Psychophysics)
Temporal order judgments (TOJs) have been used for demonstrating the facilitating effect of attention on information processing - prior entry. Prior entry is a robust, often large effect. Besides attention, other factors shorten perceptual latency, for instance stimulus saliency, action affordances of an object, or threatening objects. The expectable size for these effects is far smaller than that usually obtained for prior entry. Some effects might consist of only a few milliseconds. But are TOJs sensitive enough for detecting such small effects? For answering this question, we tested whether objects highly associated with a certain color are perceived earlier. In a four-alternative TOJ, including a "simultaneous" and "uncertain" category, we found a small advantage for high color diagnostic objects. This indicates high sensitivity of the TOJ task. We also found that "simultaneous" judgements were most sensitive. This is important for the debate on the usefulness of order vs. simultaneous judgments.

Top–down contingent attentional capture during feed-forward visual processing. - Ansorge, Ulrich; Horstmann, Gernot; Scharlau, Ingrid (Acta Psychologica)
Comments on an article by Jan Theeuwes (see record [rid]2010-20897-002[/rid]). Theeuwes summarizes an impressive number of studies demonstrating interference by irrelevant visual singletons in computer experiments with humans. Theeuwes assumes that this salience-driven capture of attention is fast and occurs within 150 ms since singleton onset, during the feed-forward phase of visual processing. In contrast to Theeuwes, we think that top–down contingent capture is the rule and explains initial and fast attention capture effects in the first feed-forward phase of visual processing. During a later phase and under some conditions exogenous capture of attention possibly follows. At the same time, we propose that the evidence presented by Theeuwes fails to support exogenous orienting because it fails to exclude a top–down contingent capture explanation. We present our arguments in two sections. One major source of evidence for top–down controlled attentional capture during the feed-forward
Keywords: visual selection; attention; information; visual field; brain; Attention; Humans; Models; Psychological; Visual Perception; Volition; Brain; Visual Field; Visual Perception; Visual Attention; Information

Rapid allocation of temporal attention in the attentional blink paradigm. - Hilkenmeier, Frederic; Scharlau, Ingrid (European Journal of Cognitive Psychology)
How fast can information of a first target (T1) in a rapid serial visual presentation be used for top-down allocation of attention in time? A valid cue about the temporal position of a second target (T2) was integrated into T1. The data show that 100 ms after T1 onset, T2 was identified better than without cue, raising the conditional T2 performance. T1 apparently triggers a facilitative effect of attention, known from other paradigms such as peripheral cueing. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: temporal attention; attentional blink paradigm; first target information; top-down allocation; rapid serial visual presentation; Stimulus Presentation Methods; Visual Stimulation; Visual Attention

Vielfalt des Schreibens. Zur Dialogizität schriftlicher Äußerungen im Spannungsfeld von Konventionalisierung und Positionierung - Karsten, Andrea

Jean Piaget, Die Entwicklung der physikalischen Mengenbegriffe beim Kinde: Erhaltung und Atomismus - Scharlau, Ingrid; Aebli, Hans (Kindlers Literatur Lexikon)

Jean Piaget, Das Erwachen der Intelligenz beim Kinde - Scharlau, Ingrid; Aebli, Hans (Kindlers Literatur Lexikon)

Early Top-Down Influences in Control of Attention: Evidence from the Attentional Blink - Hilkenmeier, Frederic; Tünnermann, Jan; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
The relevance of top-down information in the deployment of attention has more and more been emphasized in cognitive psychology. We present recent findings about the dynamic of these processes and also demonstrate that task relevance can be adjusted rapidly by incoming bottom-up information. This adjustment substantially increases performance in a subsequent task. Implications for artificial visual models are discussed.
Keywords: visuo-spatial attention; top-down control; task relevance; artificial visual attention; attentional blink

Attention Speeds Up Visual Information Processing: Selection for Perception or Selection for Action? - Weiß, Katharina; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
Attention speeds up information processing. Although this finding has a long history in experimental psychology, it has found less regard in computational models of visual attention. In psychological research, two frameworks explain the function of attention.Selection for perception emphasizes that perception- or consciousness-related processing presupposes selection of relevant information, whereas selection for action emphasizes that action constraints make selection necessary. In the present study, we ask whether or how far attention, as measured by the speed-up of information processing, is based on selection for perception or selection for action. The accelerating effect was primarily based on selection for perception, but there was also a substantial effect of selection for action.
Keywords: visuo-spatial attention; prior entry; selection for action; selection for perception

What you see is what you set – the position of moving objects - Priess, Heinz-Werner; Scharlau, Ingrid (KI 2009: Advances in Artificial Intelligence. Proceedings of the 32nd Annual Conference on Artificial Intelligence.)
Human observers consequently misjudge the position of moving objects towards the direction of motion. This so called flash-lag effect is supposed to be related to very basic processes such as processing latencies in the human brain. In our study we show that this effect can be inversed by changing the task-set of the observer. A top-down change of the observers attentional set leads to a different perception of otherwise identical scenes. Cognitive theories regard the misperception of the moving object as an important feature of attention-mediated processing, because it reflects the prioritized processing of important objects.

Jean Piaget zur Einführung - Scharlau, Ingrid

Control of Attention by Nonconscious Information: Do Intentions Play a Role? - Scharlau, Ingrid (The 5th International Conference on Computer Vision Systems)
The present study explores the deployment of attention towards nonconscious information. It is both theoretically and empirically likely that the deployment of attention can be controlled by information which is not consciously registered (attentional priming), similar to the control of sensorimotor responses by nonconscious information (response priming). However, not much is known about the functional basis of attentional priming. The present experiment explore whether and how strongly intentions (current action pans) determine whether attention is allocated towards invisible information (so called direct parameter specification). The results demonstrate that intention-mediated control is possible, but it seems to break down easily, that is to provide a weak and non-robust type of control.
Keywords: visuo-spatial attention; metacontrast; masking; intention; direct parameter specification; perceptual latency; priming

Temporal processes in prime-mask interaction: Assessing perceptual consequences of masked information. - Scharlau, Ingrid (Advances in Cognitive Psychology)
Visual backward masking is frequently used to study the temporal dynamics of visual perception. These dynamics may include the temporal features of conscious percepts, as suggested, for instance, by the asynchronous-updating model (Neumann, 1982) and perceptual-retouch theory (Bachmann, 1994). These models predict that the perceptual latency of a visual backward mask is shorter than that of a like reference stimulus that was not preceded by a masked stimulus. The prediction has been confirmed by studies using temporal-order judgments: For certain asynchronies between mask and reference stimulus, temporal-order reversals are quite frequent (e.g. Scharlau, & Neumann, 2003a). However, it may be argued that these reversals were due to a response bias in favour of the mask rather than true temporal-perceptual effects. I introduce two measures for assessing latency effects that (1) are not prone to such a response bias, (2) allow to quantify the latency gain, and (3) extend the perceptual e
Keywords: temporal processes; prime mask interaction; perceptual consequences; masked information; visual backward masking; visual perception; Temporal Lobe; Visual Masking; Visual Perception; Consequence

Experiments on the Fehrer-Raab effect and the 'Weather Station Model' of visual backward masking. - Neumann, Odmar; Scharlau, Ingrid (Psychological Research)
The Fehrer-Raab effect (simple reaction time is unaffected by metacontrast masking of the test stimulus) seems to imply that a stimulus can trigger a voluntary reaction without reaching a conscious representation. However, it is also possible that the mask triggers the reaction, and that the masked test stimulus causes a focussing of attention from which processing of the mask profits, thus reaching conscious representation earlier. This is predicted by the Weather Station Model of visual masking. Three experiments tested this explanation. Experiment 1 showed that the masked test stimulus caused a temporal shift of the mask. Experiment 2 showed that the reaction in the Fehrer-Raab effect was not exclusively triggered by a conscious representation of the test stimulus: the mask was involved in evoking the reaction. Experiment 3 again revealed a temporal shift of the mask. However, the shift was only about half as large as the Fehrer-Raab effect. The psychometric functions suggested tha
Keywords: Fehrer-Raab effect; Weather Station Model; visual backward masking; reaction time; metacontrast masking; conscious representation; Cognition; Humans; Perceptual Masking; Pilot Projects; Psychology; Experimental; Psychometrics; Reaction Time; Visual Perception; Models; Reaction Time; Visual Contrast; Visual Masking

Visual attention and the mechanism of metacontrast. - Neumann, Odmar; Scharlau, Ingrid (Psychological Research)
The U-shaped metacontrast function may result from the superimposition of two monotonic components which reflect the effects of mechanisms similar to the peripheral and central processes suggested for backward pattern masking by Turvey (Psychol Rev 80:1-52, 1973). In an experiment using the disc-ring paradigm, it was demonstrated that the decreasing and increasing branches of the metacontrast function are differently affected by the exposure duration of the mask and a task-irrelevant stimulus (distractor) appearing in the contralateral visual hemifield. The phenomenal representation of masking is different for the two parts of the curve. It is suggested that masking in the second part of the masking function, but not in the first, is related to the control of visual attention. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual attention; metacontrast; backward pattern masking; monotonic components superimposition; Attention; Contrast Sensitivity; Humans; Judgment; Perceptual Masking; Visual Perception; Metacognition; Visual Contrast; Visual Attention; Visual Masking

Perceptual latency priming: A measure of attentional facilitation. - Scharlau, Ingrid (Psychological Research)
The present paper reviews recent research on perceptual latency priming (PLP). PLP is the relative latency advantage--earlier perception--of a visual stimulus that is preceded by another, masked stimulus at its location. The first stimulus attracts attention which accelerates perception of the second stimulus. This facilitation arises even if the first stimulus is visually backward-masked by the second one. The paper summarises research on temporal and spatial properties of PLP and the question whether intentions mediate shifts of attention to external events. Possible sources of PLP besides visuo-spatial attention are discussed. Finally, I give a review of feedforward and reentrant models of PLP and compare them to the empirical evidence. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: perceptual latency priming; attentional facilitation; visuospatial attention; visual backward masking; prior entry; Attention; Humans; Judgment; Reaction Time; Space Perception; Attention; Priming; Response Latency; Visual Masking; Visuospatial Ability

Trends and styles in visual masking. - Scharlau, Ingrid; Ansorge, Ulrich; Breitmeyer, Bruno G. (Advances in Cognitive Psychology)
The topic of the present edition is visual masking paradigms-as powerful tool for demonstrating the processing of nonconscious visual information. In the present issue one article presents an improved methodology for disentangling perceptual and temporal influences in markers. Another paper demonstrates that preemptive control, or DPS, mediates the allocation of attention towards possible targets. One of the contributions specify conditions under which DPS-like effects are found as opposed to conditions under which stimulus-driven effects are found. A study of two illusions which the prime may cause in a trailing stimulus, a temporal pre-dating of the mask and a perception of motion in later stimuli adjacent to the prime is presented in the issue. Another contribution addresses how the percept of a stimulus is altered by a temporal and spatial interplay of two backward masks or of one forward mask and two backwards masks. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual masking; visual information; attention; stimulus-driven effects; motion perception; Attention; Illusions (Perception); Motion Perception; Visual Masking

Latency facilitation in temporal-order judgments: Time course of facilitation as a function of judgment type. - Scharlau, Ingrid; Ansorge, Ulrich; Horstmann, Gernot (Acta Psychologica)
The paper is concerned with two models of early visual processing which predict that priming of a visual mask by a preceding masked stimulus speeds up conscious perception of the mask (perceptual latency priming). One model ascribes this speed-up to facilitation by visuo-spatial attention [Scharlau, I., & Neumann, O. (2003a). Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional explanation. Psychological Research 67, 184-197], the other attributes it to nonspecific upgrading mediated by retino-thalamic and thalamo-cortical pathways [Bachmann, T. (1994). Psychophysiology of visual masking: The fine structure of conscious experience. Commack, NY: Nova Science Publishers]. The models make different predictions about the time course of perceptual latency priming. Four experiments test these predictions. The results provide more support for the attentional than for the upgrading model. The experiments further demonstrate that testing latency facilitation w
Keywords: latency facilitation; temporal order judgments; visual processing; priming; conscious perception; visual mask; Adult; Attention; Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Space Perception; Time Perception; Visual Perception; Consciousness States; Judgment; Priming; Visual Masking; Temporal Order (Judgment)

More efficient rejection of happy than of angry face distractors in visual search. - Horstmann, Gernot; Scharlau, Ingrid; Ansorge, Ulrich (Psychonomic Bulletin & Review)
In the present study, we examined whether the detection advantage for negative-face targets in crowds of positive-face distractors over positive-face targets in crowds of negative faces can be explained by differentially efficient distractor rejection. Search Condition A demonstrated more efficient distractor rejection with negative-face targets in positive-face crowds than vice versa. Search Condition B showed that target identity alone is not sufficient to account for this effect, because there was no difference in processing efficiency for positive- and negative-face targets within neutral crowds. Search Condition C showed differentially efficient processing with neutral-face targets among positive- or negative-face distractors. These results were obtained with both a within-participants (Experiment 1) and a between-participants (Experiment 2) design. The pattern of results is consistent with the assumption that efficient rejection of positive (more homogenous) distractors is an im
Keywords: angry face distractors; visual search; negative face distractors; Adult; Anger; Attention; Face; Female; Happiness; Humans; Male; Rejection (Psychology); Visual Perception; Distraction; Face Perception; Visual Perception; Visual Search

Visual search for a motion singleton among coherently moving distractors. - Ansorge, Ulrich; Scharlau, Ingrid; Labudda, Kirsten (Psychological Research)
In the current study, we tested whether search for a visual motion singleton presented among several coherently moving distractors can be more efficient than search for a motion stimulus presented with a single distractor. Under a variety of conditions, multiple spatially distributed and coherently moving distractors facilitated search for a uniquely moving target relative to a single-motion-distractor condition (Experiments 1,3, and 4). Color coherencies among static distractors were not equally effective (Experiments 1 and 2). These results confirm that humans are highly sensitive to antagonistically directed motion signals in backgrounds compared with spatially more confined regions of visual images. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual search; motion singleton; visual images; visual motion; coherently moving distractors; Adult; Attention; Exploratory Behavior; Female; Humans; Male; Motion Perception; Visual Perception; Motion Perception; Stimulus Salience; Visual Search; Distraction; Retinal Image

Perceptual latency priming and illusory line motion: Facilitation by gradients of attention? - Scharlau, Ingrid; Horstmann, Gernot (Advances in Cognitive Psychology)
The phenomena of illusory line motion and perceptual latency priming are both assumed to reflect a facilitation of perceptual latency. The explanation of illusory line motion presupposes that attention is distributed in a gradient fashion whereas this is not a necessary part of the explanation of perceptual latency priming. Two experiments test whether an attentional gradient is present in perceptual latency priming. Evidence for a gradient was found within 2.5° of visual angle around the attended location, but not at a distance of 5° and more. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: perceptual latency priming; illusory line motion; attention; visual angle; Illusions (Perception); Priming; Visual Field; Visual Perception; Visual Attention; Spatial Orientation (Perception)

Evidence for split foci of attention in a priming paradigm. - Scharlau, Ingrid (Perception & Psychophysics)
Most models of visuospatial attention include the notion that attention is dedicated to a single location in space. However, several researchers have found evidence that under appropriate circumstances, attention may be allocated to noncontiguous locations (e.g., Awn & Pashler, 2000; Bichot, Cave, & Pashler, 1999; Kramer & Hahn, 1995). In the present experiments, the spatial distribution of attention was assessed by a novel method, perceptual latency priming: the latency benefit of an attended visual stimulus, as compared with a nonattended stimulus. Experiment 1 assessed whether observers are able to attend to two nonadjacent regions or a region of variable size. Experiment 2 tested whether, when two distant locations are attended to, the region between them is necessarily also in the focus of attention. Two further experiments controlled for objections against the method used and replicated the main results of the first two experiments. The experiments showed a robust attentional pr
Keywords: visuospatial attention; priming paradigm; spatial distribution; Adult; Attention; Female; Humans; Male; Attention; Priming; Spatial Perception; Visuospatial Ability

Illusory line motion and perceptual latency priming: Two alternative measures for attentional facilitation - Scharlau, Ingrid (Dynamic Perception 2004: Workshop of GI section 1.0.4 "Image Understanding" and the European Networks MUHCI and ECOVISION)

Evidence against response bias in temporal order tasks with attention manipulation by masked primes. - Scharlau, Ingrid (Psychological Research)
Attending to a location shortens the perceptual latency of stimuli appearing at this location (perceptual latency priming). According to attentional explanations, perceptual latency priming relies on the speeded transfer of attended visual information into an internal model. However, doubts about the attentional origin have repeatedly been raised because efforts to minimize response bias have been insufficient in most studies. Five experiments investigated the contribution of a response bias to perceptual latency priming (judgment bias due to the two-alternative forced-choice method and due to the existence of the prime, criterion effects or second-order bias, sensorimotor priming). If any, only small response biases were found. The results thus support the attentional explanation. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: response bias; temporal order tasks; attention manipulation; masked primes; perceptual latency priming; Adult; Attention; Discrimination Learning; Female; Humans; Male; Memory; Short-Term; Orientation; Pattern Recognition; Visual; Perceptual Masking; Psychomotor Performance; Psychophysics; Reaction Time; Serial Learning; Attention; Latent Learning; Priming; Response Bias; Visual Perception; Response Latency; Temporal Order (Judgment)

The spatial distribution of attention in perceptual latency priming. - Scharlau, Ingrid (The Quarterly Journal of Experimental Psychology A: Human Experimental Psychology)
The spatial distribution of visual attention is a yet unresolved question. One of the main topics is whether attention is distributed in a graded fashion around an attended location (e.g., Downing, 1988; Zimba & Hughes, 1987). The present experiments explore whether, and on which conditions, gradients of attention arise and contribute to perceptual facilitation. A masked or unmasked prime precedes one of two targets whose temporal order has to be judged. The prime captures attention, which shortens the perceptual latency of the primed target (perceptual latency priming; Scharlau & Neumann, 2003a; Shore, Spence, & Klein, 2001). No strong evidence for an attentional gradient was found. (1) Accuracy of temporal order judgements was independent of the distance between the two targets that were judged. That is, facilitation of the second target by the first target was spatially invariant. (2) With targets of short duration, facilitation was independent of prime-target distance. (3) With ta
Keywords: visual attention; spatial distribution; perceptual latency priming; Attention; Priming; Spatial Organization; Visual Perception

Reaktionszeitmessung: Allgemeinpsychologische Grundlage und psycholinguistische Anwendungen - Scharlau, Ingrid; Ansorge, Ulrich; Neumann, Odmar (Psycholinguistik – Psycholinguistics)

Direct parameter specification of an attention shift: Evidence from perceptual latency priming. - Scharlau, Ingrid; Ansorge, Ulrich (Vision Research)
In the direct parameter specification (DPS) mode of sensorimotor control, response parameters can be specified by stimuli that are not consciously perceived [Psychological Research/Psychologische Forschung 52 (1990) 207]. DPS is contingent on the current intentions. The invisible stimuli can be processed for the purposes of sensorimotor control only if they match the actual intentions, for example, share task-relevant features. The present experiments explore whether attentional capture by masked abrupt-onset stimuli is mediated via DPS. Participants judged which of two visual targets appeared first. Masked primes preceded one of the targets. The primes were either similar to the targets or not, in shape, or in color. Target-like (task-relevant), but not distractor-like (task-irrelevant), primes facilitated perceptual latencies of targets trailing at their positions. Thus, the latency effects resulted from DPS of an attention shift, rather than from bottom-up capture or from top-down
Keywords: direct parameter specification; DPS; attention shift; latency priming; sensorimotor control; stimuli; task-relevant features; visual targets; color; shape; latency effects; Adult; Attention; Discrimination (Psychology); Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Visual Perception; Attention; Perceptual Motor Processes; Response Latency; Stimulus Onset; Visual Stimulation; Form and Shape Perception; Sensory Adaptation

Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional interpretation. - Scharlau, Ingrid; Neumann, Odmar (Psychological Research)
Four experiments investigated the influence of a metacontrast-masked prime on temporal order judgments. The main results were (1) that a masked prime reduced the latency of the mask's conscious perception (perceptual latency priming), (2) that this effect was independent of whether the prime suffered strong or weak masking, (3) that it was unaffected by the degree of visual similarity between the prime and the mask, and that (4) there was no difference between congruent and incongruent primes. Finding (1) suggests that location cueing affects not only response times but also the latency of conscious perception. (2) The finding that priming was unaffected by the prime's detectability argues against a response bias interpretation of this effect. (3) Since visual similarity had no effect on the prime's efficiency, it is unlikely that sensory priming was involved. (4) The lack of a divergence between the effects of congruent and incongruent primes implies a functional difference between t
Keywords: perceptual latency priming; temporal order judgments; masked stimuli; unmasked stimuli; attentional interpretation; response times; location cueing; visual perception; Adult; Attention; Female; Humans; Male; Models; Psychological; Perceptual Masking; Psychometrics; Reaction Time; Task Performance and Analysis; Time Perception; Masking; Reaction Time; Response Latency; Stimulus Parameters; Visual Contrast; Attention; Cues; Priming; Temporal Frequency; Temporal Order (Judgment)

Temporal parameters and time course of perceptual latency priming. - Scharlau, Ingrid; Neumann, Odmar (Acta Psychologica)
Visual stimuli (primes) reduce the perceptual latency of a target appearing at the same location (perceptual latency priming, PLP). Three experiments assessed the time course of PLP by masked and, in Experiment 3, unmasked primes. Experiments 1 (N=11; mean age 26.9) and 2 (N=12; mean age 25.6) investigated the temporal parameters that determine the size of priming. Stimulus onset asynchrony was found to exert the main influence accompanied by a small effect of prime duration. Experiment 3 (N=19; mean age 27.7) used a large range of priming onset asynchronies. We suggest to explain PLP by the Asynchronous Updating Model which relates it to the asynchrony of 2 central coding processes, preattentive coding of basic visual features and attentional orienting as a prerequisite for perceptual judgments and conscious perception. (PsycINFO Database Record (c) 2017 APA, all rights reserved)
Keywords: perceptual latency priming; temporal parameters; Asynchronous Updating Model; time course; stimulus onset asynchrony; visual masking; attention; Adult; Attention; Female; Humans; Male; Perceptual Masking; Reaction Time; Time Perception; Visual Perception; Attention; Priming; Stimulus Onset; Visual Masking; Visual Perception; Models; Time

Influences of visibility, intentions, and probability in a peripheral cuing task. - Ansorge, Ulrich; Heumann, Manfred; Scharlau, Ingrid (Consciousness and Cognition: An International Journal)
According to the concept of direct parameter specification, nonconsciously registered information can be processed to the extent that it matches currently active intentions of a person. This prediction was tested and confirmed in the current study. Masked visual information provided by peripheral cues led to reaction time (RT) effects only if the information specified one of the required responses (Experiments 1 and 3). Information delivered by the same masked cues that did not match the intentions was not used. However, the same information influenced RT if it was provided by visible cues (Experiments 2 and 3). The results suggest that the processing of nonconsciously registered information is flexible because it is susceptible to the changing intentions of a person. Yet, these processes are apparently restricted as nonconsciously registered information cannot be used as easily for purposes not corresponding to the currently active intentions as better visible information. (PsycINFO
Keywords: active intentions; cues; direct parameter specification; nonconscious processing ability; Adult; Consciousness; Female; Humans; Male; Mental Processes; Perceptual Masking; Photic Stimulation; Visual Perception; Awareness; Cognitive Processes; Cues; Intention; Consciousness States; Probability

Exogenous and intention-dependent control of attention shifts in dynamic displays - Scharlau, Ingrid; Ansorge, Ulrich (Dynamic Perception: Workshop of GI section 1.0.4 "Image Understanding" and the European Networks MUHCI and ECOVISION)

Leading, but not trailing, primes influence temporal order perception: Further evidence for an attentional account of perceptual latency priming. - Scharlau, Ingrid (Perception & Psychophysics)
Presenting a masked prime leading a target influences the perceived onset of the masking target. This priming effect is explained by the asynchronous updating model: The prime initiates attentional allocation toward its location, which renders a trailing target at the same place consciously available earlier. In 3 experiments, this perceptual latency priming by leading primes was examined jointly with the effects of trailing primes in order to compare the explanation of the asynchronous updating model with the onset-averaging and the P-center hypotheses. Exp 1 (n=15, mean age 27.1 yrs) showed that an attended, as well as an unattended, prime leads to perceptual latency priming. In addition, a large effect of trailing primes on the onset of a target was found. As Exp 2 (n=13, mean age 26.5 yrs) demonstrated, this effect is quite robust, although smaller than that of a leading prime. In Exp 3 (n=13, mean age 24.8 yrs), masked primes were used. Under these conditions, no influence of tra
Keywords: attention; leading primes; trailing primes; temporal order perception; perceptual latency priming; Adult; Attention; Female; Fixation; Ocular; Humans; Male; Perceptual Masking; Random Allocation; Time Perception; Visual Perception; Attention; Masking; Priming; Stimulus Frequency; Temporal Frequency; Temporal Order (Judgment)

Familien mit Kindern im frühen Erwachsenenalter - Papastefanou, Christiane; Buhl, Heike M. (Lehrbuch Familienbeziehungen. Eltern und Kinder in der Entwicklung)

Visual conscious perception could be grounded in a nonconscious sensorimotor domain - Ansorge, Ulrich; Scharlau, Ingrid; Heumann, Manfred; Klotz, Werner (Behavioral and Brain Sciences)
Visual conscious perception could be grounded in a nonconscious sensorimotor domain. Although invisible, information can be processed up to the level of response activation. Moreover, these nonconscious processes are modified by actual intentions. This notion bridges a gap in the theoretical framework of O'Regan & Noë.

Erkenntnistheorie als Wissenschaft: Streitpunkte zwischen Husserl, Gurwitsch, Merleau-Ponty und Piaget - Scharlau, Ingrid

Die genetische Epistemologie Jean Piagets in der Perspektive der Vernunftkritik - Scharlau, Ingrid (Grundlinien der Vernunftkritik)

Cyberspace - Scharlau, Ingrid (Deep Storage - Arsenale der Erinnerung - Sammeln, Speichern, Archivieren in der Kunst)

Piaget lesen - Scharlau, Ingrid (Information Philosophie)

Jean Piaget zur Einführung - Scharlau, Ingrid

Cartesianische Grundlagen der wissenschaftlichen Psychologie - Scharlau, Ingrid